2021
DOI: 10.21608/ejhc.2021.146731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nursing Counseling Guided by BETTER Model on Sexuality, Marital Satisfaction and Psychological Status among Breast Cancer Women

Abstract: Background: Breast cancer is one of the main problems related to women's health, and the various forms of treatment can lead to bodily changes and significantly alter women's sexuality and psychological status. Aim: The aim of this study was to evaluate the effect of nursing counseling guided by BETTER model on sexuality, marital Satisfaction and psychological status among breast cancer women. Design: A quasi-experimental research design. Setting: The study was conducted at an Outpatient clinic, Oncology Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This may be due to the economic and living conditions experienced in recent years that require working longer hours to provide the needs of the family. This was consistent with Shahin, et al, (2021), who reflected that nursing counseling had substantial influence on enhancing breast cancer women's sexuality, marital satisfaction and psychological condition. Also, this finding was supported by study done by EidFarrag, et al, (2018), they reflected that martial relations (marital intimacy and adjustment), sexuality and spousal support were improved at three and six months following intervention with statistically significant differences.…”
Section: Effect Of Psychological Counseling On Depressive Symptoms An...supporting
confidence: 83%
“…This may be due to the economic and living conditions experienced in recent years that require working longer hours to provide the needs of the family. This was consistent with Shahin, et al, (2021), who reflected that nursing counseling had substantial influence on enhancing breast cancer women's sexuality, marital satisfaction and psychological condition. Also, this finding was supported by study done by EidFarrag, et al, (2018), they reflected that martial relations (marital intimacy and adjustment), sexuality and spousal support were improved at three and six months following intervention with statistically significant differences.…”
Section: Effect Of Psychological Counseling On Depressive Symptoms An...supporting
confidence: 83%
“…In this regard, Shahin et al . [ 32 ] found that nursing counseling with the BETTER model had a considerable effect on improving the sexual desire, sexual satisfaction, and psychological status of women with breast cancer. They indicated that although the BETTER model was designed for a specific group of patients and specialists, it had also been considered in other chronic diseases owing to its simplicity and focus on sexual discourse.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Shahin et al found that nursing counseling with the BETTER model had a considerable effect on improving sexual desire, sexual satisfaction, and psychological status of women with breast cancer. They indicated that although the BETTER model was designed for a speci c group of patients and specialists, it had also been considered in other chronic diseases owing to its simplicity and focus on sexual discourse (23). Zamani et al (2020) found that the BETTER model-based couple training and counseling were effective in improving sexual satisfaction of women with type 1 diabetes, and the effect remained until 3 months after the intervention (24).…”
Section: Discussionmentioning
confidence: 99%